(untitled) (Research, Society and Development, 2021)
Candidemia is a current concern in hospitals around the world, with a recurrent distribution of Candida species in ICU patients and a high mortality rate. This study aimed to identify Candida species, risk factors, and antifungal resistance rates in the State of Rio Grande do Norte, Brazil. This is an analytical descriptive cross-sectional study, carried out from 2018 to 2020, with 50 patients admitted to ICUs of three tertiary hospitals, in the city of Natal, State of Rio Grande do Norte, Brazil. No statistical differences were related to sex, but it was related to age group, especially in those under eleven years old. Candida albicans (48%), C. tropicalis (32%), and C. pelliculosa (6%) were the most prevalent species. The main risk factor for candidemia observed in the study was the use of urinary catheters (94%), parenteral nutrition (84%), a central venous catheter (48%), corticotherapy (44%), and immunosuppression (44%). No significant statistical difference in the distribution of deaths when compared to the hospitals and the presentation of Candida species. Thus, special attention must be directed to patients who present these risk factors in order to undergo a previous prophylactic therapy. The percentage of deaths was 16.67% in Hospital B, 25% in Hospital C, and 0% for patients in Hospital A. In Candida albicans the phenomenon of antifungal resistance was related to anidulafungin, micafungin, voriconazole, and amphotericin B, as well as from C. tropicalis to these last two antifungals. Candida pelliculosa was also resistant to voriconazole. While C. parapsilosis and C. krusei showed resistance to anidulafungin. The species distribution and antifungal susceptibility of Candida isolated from candidemia cases bring new perspectives to the understanding of this serious scenario. Thus, it provides useful information on the epidemiology, risk factors, and susceptibility pattern useful for the selection of empirical antifungal agents for patients with candidemia.